1981
DOI: 10.2340/0001555561353354
|View full text |Cite
|
Sign up to set email alerts
|

Successful treatment of actinic reticuloid induced by whole-body topical application of mechlorethamine

Abstract: A man suffering from actinic reticuloid for 2 years showed highly abnormal light sensitivity over a broad action spectrum. He has been successfully treated with daily whole-body topical applications of mechlorethamine, initially for 4 weeks and after a 2-month interruption, for 3 weeks. Gauzes moistened with the same solution were placed over lichenified areas for 10-15 min. His skin became normal pale and the lichenification decreased. After treatment his tolerance for daylight increased.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

1993
1993
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…Topical corticosteroids are offered in a range of potencies, from low‐potency steroids including fluocinolone acetonide 11 . to high‐potency steroids, such as clobetasole propionate 12 . With the utilization of hydrocolloid 12 or occlusive dressings made of plastic wrap, topical corticosteroids' absorption has been further improved.…”
Section: Discussionmentioning
confidence: 99%
“…Topical corticosteroids are offered in a range of potencies, from low‐potency steroids including fluocinolone acetonide 11 . to high‐potency steroids, such as clobetasole propionate 12 . With the utilization of hydrocolloid 12 or occlusive dressings made of plastic wrap, topical corticosteroids' absorption has been further improved.…”
Section: Discussionmentioning
confidence: 99%
“…The occlusive dressing group did not demonstrate therapeutic superiority 14 . Nevertheless, in the observational study, clobetasol propionate and hydrocolloid occlusive dressing once a week led to the complete remission of disease in 89% of patients in 2 weeks 15 . Flurandrenolone tape used in the treatment of lichen simplex chronicus was well‐known.…”
Section: Introductionmentioning
confidence: 94%
“…The latest systematic review of treatments for lichen simplex chronicus pointed out that there was a lack of high‐quality, evidence‐based treatments for lichen simplex chronicus 1 . In the latest review, one RCT and one observational study examined the use of occlusion as adjunctive therapy with topical steroids showed conflicting outcomes 1,14,15 . In the RCT, treatment with 0.3% diflucortolone valerate twice daily with and without plastic occlusion was investigated.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations